ChemInform Abstract: Core‐Scaffold‐Inspired Asymmetric Synthesis of Polysubstituted Chiral Hexahydropyridazines that Potently Inhibit Breast Cancer Cell Proliferation by Inducing Apoptosis. Issue 17 (April 2016) - Leng, Hai‐Jun; Peng, Fu; Zingales, Sarah; Huang, Wei; Wang, Biao; Zhao, Qian; Zhou, Rui; He, Gu; Peng, Cheng; Han, Bo
Abstract: This asymmetric cascade approach utilizes an organocatalytic Michael reaction followed by intermolecular α‐amination and intramolecular hemiaminalization to yield chiral pyridazines with four or five contiguous stereogenic centers.